Effects of Aspects on Diversity and Soil Carbon Stock in a Degraded forest of Aravalli in Rajasthan, India - Singh, G.; Singh, Kaushal (Indian Forester, 2013)
Because of southwest - northeast orientation of Aravalli hill in Rajasthan, aspect effects may be an important factor in forest growth and composition. To study the effect of aspect on tree and shrub diversity and consequent effect on soil carbon storage a study was carried out in Borawad Forest block in Pali Forest Division, Rajasthan. Twenty five plots of 0.1 ha area were laid at 200 m interval at both east-west (longitude) and north-south (latitude) directions. Based on the slope facing in a particular direction, these plots were categorized into north-east (NE), south-east (SE), south-west (SW) and North-west (NW). The study indicate that the aspect affected the distribution patterns of incoming solar radiation and water balances, resulting in changes in vegetation pattern. Though this forest represents Anogeisus pendula type of forest, but there were wide variation the species dominance in different aspects that is preferred by different species. Southeast (SE) aspect were more suitable for tree diversity whereas shrub diversity and their population were highest on southwest aspect indicating that shrubs species prefers relatively xeric environment. Soil carbon stock was highest on southeast followed by southwest aspects showing strong relation with tree and shrub diversity.